P26 Increased insulin sensitivity in the endothelium reduces no bioavailability via AKT/PYK2/NOX2 signalling loop. (26th October 2016) - Tang, KY; Viswambharan, H; Yuldasheva, N; Imrie, H; Sukumar, P; Gauge, M; Sengupta, A; Skromna, A; Shah, P; Galloway, S; Smith, J; Porter, K; et al.
Abstract : Type 2 Diabetes is one of the major contributors to cardiovascular diseases. Insulin stimulates generation of the anti-atherosclerotic signalling molecule, nitric oxide (NO). Aim: We assessed the effect of increasing insulin sensitivity specifically in the endothelium on NO bioavailability and vascular function. We generated a novel transgenic mouse over-expressing type A human Insulin Receptor (HIRECO) in the endothelium, driven by the Tie-2 promoter-enhancer. Method: Fresh tissues and isolated pulmonary endothelial cells from the HIRECO mice were analysed using western blotting and organ baths were used to study the effects of insulin sensitivity in vascular function. Results: HIRECO mice demonstrated no significant metabolic abnormalities compared to wild type littermates. HIRECO mice had endothelial dysfunction with a blunted response to acetylcholine (Ach). This impaired aortic response to Ach was normalised by the NADPH oxidase inhibitor peptide, gp91ds-tat. A significant decrease in insulin-mediated eNOS phosphorylation was also detected in these mice, in spite of basal eNOS phosphorylation in endothelial cells. MK-2206, Akt inhibitor reduced PYK2 expression revealing a new signalling loop linked to enhanced insulin signalling involving Akt, Nox2 and PYK2 contributing to reduce the basal and stimulated NO bioactivity. Knockdown of PYK2 in HIRECO endothelial cells with siRNA significantly reduced NOX2 expression. Conclusion: These data clearly suggest that increased endothelial insulin signalling, leads to vascular dysfunction. For the first time, we have demonstrated that increased insulin sensitivity specifically in the endothelium leads to detrimental effects on the vascular endothelial integrity, reducing NO bioactivity and promotes atherosclerosis.